Implementasi Fungsi Manajemen Dalam Meningkatkan Kualitas Program Tahfidz di SMP Islam Internasional Al Abidin Sragen - Rahma Fadilla Chairunisa; Hakimuddin Salim (Jayapangus Press, 2026)
This study aims to examine the application of management functions in improving the quality of the Al-Quran memorization program at Al Abidin International Junior High School, Sragen. The study used a qualitative approach through a case study. Data collection was conducted through in-depth interviews, comprehensive observations, and documentation, which were then analyzed using the Miles and Huberman interactive model. The validity of the measurement data used triangulation. The results of the study indicate that the integration of management functions including planning, organizing, implementing, and evaluating has proven effective in significantly improving the quality of the tahfidz program. Planning was carried out by establishing tahfidz as the school's flagship program; organization was realized through the formation of a management structure involving the principal, coordinator, and tahfidz teachers; the implementation of learning applied four methods, namely talaqqi, tikrar, ziyadah, and muroja’ah; and evaluation was carried out periodically through daily and periodic assessments. The success of the program was supported by teacher competence, student motivation, and a conducive environment. However, its implementation still faces several obstacles, including limited time for tahsin learning, accumulation of student motivation, and reflecting memorization abilities among students. This research contributes to the development of Islamic education management, particularly in providing a model of integration of management functions that can be adapted by other Al-Quran-based educational institutions.